Analysis of 14-bp HLA-G polymorphism in middle-eastern women with recurrent implantation failure - Sulaiman, Rand; Mohammad, Tharaa; Alhalabi, Marwan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Implantation appears to be the major rate-limiting step in assisted reproductive techniques success. Recurrent implantation failure (RIF) is a common condition, being the failure to achieve a clinical pregnancy after transfer of four or more good-quality embryos in a minimum of two IVF cycles in a woman under the age of 40. Human leukocyte antigen G (HLA-G) is thought to play a key role in implantation by modulating cytokine secretion to enable the semi-allogeneic embryo to implant into the maternal endometrium. The aim of this study was to investigate the association between the 14-bp ins/del HLA-G polymorphism and rates of RIF. No similar studies were conducted nationally or regionally. Methods: The study was designed as a case-control study. A proportion of 30 patients with RIF were selected as the experimental group. The control group included 15 patients with at least one pregnancy following IVF procedure. Peripheral blood samples were collected from both groups. DNA was extracted and the polymorphism analysis was performed using (AMPLI - HLA-G polymorphism) kit, then PCR products were electrophoresed on 2% agarose gel. statistical analysis was performed using SPSS statistics software. Results: A total of 45 middle-eastern patients were recruited in this case-control study. High frequency of the polymorphism was found in both case (76.6%) and control (86.67%) groups, but with no significant difference between the two groups (p=0.429). Conclusions: There is no correlation between the 14-bp ins/del HLA-G polymorphism and RIF, thus it may be considered as a normal polymorphism and might not affect the level of HLA-G.